Cost-effectiveness of Remdesivir and Dexamethasone for COVID-19 Treatment in South Africa. (29th January 2021) - Jo, Youngji; Jamieson, Lise; Edoka, Ijeoma; Long, Lawrence; Silal, Sheetal; Pulliam, Juliet R C; Moultrie, Harry; Sanne, Ian; Meyer-Rath, Gesine; Nichols, Brooke E
Abstract: Background: Dexamethasone and remdesivir have the potential to reduce coronavirus disease 2019 (COVID)–related mortality or recovery time, but their cost-effectiveness in countries with limited intensive care resources is unknown. Methods: We projected intensive care unit (ICU) needs and capacity from August 2020 to January 2021 using the South African National COVID-19 Epi Model. We assessed the cost-effectiveness of (1) administration of dexamethasone to ventilated patients and remdesivir to nonventilated patients, (2) dexamethasone alone to both nonventilated and ventilated patients, (3) remdesivir to nonventilated patients only, and (4) dexamethasone to ventilated patients only, all relative to a scenario of standard care. We estimated costs from the health care system perspective in 2020 US dollars, deaths averted, and the incremental cost-effectiveness ratios of each scenario. Results: Remdesivir for nonventilated patients and dexamethasone for ventilated patients was estimated to result in 408 (uncertainty range, 229–1891) deaths averted (assuming no efficacy [uncertainty range, 0%–70%] of remdesivir) compared with standard care and to save $15 million. This result was driven by the efficacy of dexamethasone and the reduction of ICU-time required for patients treated with remdesivir. The scenario of dexamethasone alone for nonventilated and ventilated patients requires an additional $159 000 and averts 689 [uncertainty range, 330–1118] deaths, resulting in $231 per death averted, relative to standard care. Conclusions: The use of remdesivir for nonventilated patients and dexamethasone for ventilated patients is likely to be cost-saving compared with standard care by reducing ICU days. Further efforts to improve recovery time with remdesivir and dexamethasone in ICUs could save lives and costs in South Africa.